Optimization and kinetics modeling of phenolics extraction from coffee silverskin in deep eutectic solvent using ultrasound-assisted extraction - Supawat Taweekayujan; Supitcha Somngam; Tanawan Pinnarat (My University, 2023)
This research investigates the effect of extraction parameters on total phenolic content (TPC) and the antioxidant capacity of coffee silverskin (CS) extract using ultrasound-assisted extraction (UAE) in deep eutectic solvent (DES). The optimization was carried out in two stages: (i) the optimization of the UAE condition with the highest TPC; and (ii) a four-factor Box-Behnken design (BBD) to optimize the UAE condition with the optimal TPC; 2,2 diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity; and ferric reducing antioxidant power (FRAP). The results showed that the optimal UAE condition with the highest TPC was 150-250 μm CS particle size; 1,6-hexanediol as hydrogen bond donor (HBD); 1:7 HBA:HBD molar ratio; and 30% (w/w) water content, given choline chloride (ChCl) as hydrogen bond acceptor (HBA), 30 min extraction time and 3
Keywords: Deep eutectic solvent; Ionic liquids properties and applications